Kaonic atoms – studies of the strong interaction with strangeness - Marton J.; Bazzi M.; Beer G.; Berucci C.; Bragadireanu A.M.; Cargnelli M.; Curceanu C.; d’Uffizi A.; Fiorini C.; Ghio F.; Guaraldo C.; Hayano R.; et al. (EPJ Web of Conferences, 2014)
The strong interaction of charged antikaons (K−) with nucleons and nuclei in the low-energy regime is a fascinating topic. The antikaon plays a peculiar role in hadron physics due to the strong attraction antikaon-nucleon which is a key question for possible kaonic nuclear bound states. A rather direct experimental access to the antikaon-nucleon scattering lengths is provided by precision X-ray spectroscopy of transitions to low-lying states in light kaonic atoms like kaonic hydrogen and deuterium. After the successful completion of precision measurements on kaonic hydrogen and helium isotopes by SIDDHARTA at DAΦNE/LNF, new X-ray studies with the focus on kaonic deuterium are in preparation (SIDDHARTA2). In the future with kaonic deuterium data the antikaon-nucleon isospin-dependent scattering lengths can be extracted for the first time. An overview of the experimental results of SIDDHARTA and an outlook to future perspectives in the SIDDHARTA2 experiments in this frontier research field will be given.